Regional Legal Politic Problems Concerning the Rights of Customary Law Communities in Majene Regency, West Sulawesi Province - Astomo, Putera Astomo; Rizal Putri, Faradillah; Sungkharat, Utit (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
The Majene Regency Government established the Regional Regulation of Majene Regency West Sulawesi Province Number 1 of 2023 concerning Recognition of Protection and Empowerment of Customary Law Communities, but this caused problems, receiving a lot of criticism from various groups regarding the recognition mechanism for Customary Law Communities, which had an impact on the rights of Customary Law Communities in the Regency. Majene, West Sulawesi Province. This research aims to determine and analyze the regional legal politics related to the recognition and protection of Customary Law Communities in Majene Regency, West Sulawesi Province. Besides that, the impacts arising from the implementation of regional regulations on the rights of Customary Law Communities in Majene Regency, West Sulawesi Province. The type of research is doctrinal/normative legal research, the approach method used is legislations (statute approach), and primary data obtained at the West Sulawesi Province Legal Documentation and Information Network (JDIH). The results of this research, namely the impact arising from the implementation of the regional regulation on the rights of Customary Law Communities in Majene Regency, West Sulawesi Province, is that this regional regulation is detrimental to the rights of Customary Law Communities, such as not adhering to an independent identification system (self-identification) regarding the existence of Customary Law Communities. Apart from that, the identification, verification and validation teams for Customary Law Communities regulated in this regional regulation were not related to each other or in other words did not form a unified whole.